The Role of Regional Organizations in Disaster Risk Management - Hollis, S. author. aut Link
XII, 242 p.
Keywords: The use of regional organizations to mitigate and respond to disasters has become a global trend. This book examines the role regional organizations play in managing disaster risk through a comparative study of ten regional organizations, demonstrating their current limitations and future potential.